Upstream dam impacts on gilded catfish Brachyplatystoma rousseauxii (Siluriformes: Pimelodidae) in the Bolivian Amazon - Van Damme, Paul A. (2019)
This paper explores the effects of two run-of-river dams (Jirau and Santo Antônio) built in cascade in the middle Madeira River (Brazil) on the interruption of long-distance migration routes of the gilded catfish (Brachyplatystoma rousseauxii). A participative monitoring system was set up to compare capture by commercial fishers approximately 1500 km upstream ofthe dams in Bolivia, before (1998-2007) and after (2015-2017) dam closure. A significant decrease in gilded catfish catches and in catch per unit effort was observed after dam closure, whereas no significant difference in mean weight was found. Back-estimation of age suggests that the few individuals remaining after dam closure in 2009 are a mixture of old homers that returned upstream before dam closure, and residents hatched after dam closure and trapped in the upper Madeira. Unless fishways in the Madeira River dams improve their efficiency, the gilded catfish might become rare and in danger of regional extinction in the upper Madeira basin in the next few years, negatively affecting river fisheries.